2023
DOI: 10.1007/s11154-023-09792-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and malabsorptive gastrointestinal conditions: A bidirectional relationship?

Abstract: This paper is one of the outcomes of the 5th International Conference "Controversies in Vitamin D" held in Stresa, Italy from 15 to 18 September 2021 as part of a series of annual meetings which was started in 2017. The scope of these meetings is to discuss controversial issues about vitamin D. Publication of the outcomes of the meeting in international journals allows a wide sharing of the most recent data with the medical and academic community. Vitamin D and malabsorptive gastrointestinal conditions was one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 125 publications
0
7
0
1
Order By: Relevance
“…After bariatric surgery, a minimum of 60 g of protein per day is recommended to maintain favorable albumin levels [ 51 , 53 , 54 ]. It is recommended to monitor protein intake and albumin presence before and after surgical procedures, together with a balanced diet [ 55 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…After bariatric surgery, a minimum of 60 g of protein per day is recommended to maintain favorable albumin levels [ 51 , 53 , 54 ]. It is recommended to monitor protein intake and albumin presence before and after surgical procedures, together with a balanced diet [ 55 ].…”
Section: Reviewmentioning
confidence: 99%
“…The incidence of deficiency is around 50% to 70% at two to four years. Vitamin A deficiency is most frequent in third-world countries and people with liver storage diseases [ 55 ]. The clinical manifestation of vitamin A deficiency is more notable and frequent than that of vitamin K [ 40 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D is a crucial hormone with skeletal and extraskeletal effects [ 91 ]. The most relevant skeletal action of vitamin D is an increase in intestinal calcium absorption and bone mineralization [ 92 ]. Its deficiency, when severe, may cause rickets in children and osteomalacia in adults.…”
Section: Treatment Of Acromegaly-related Osteopathymentioning
confidence: 99%
“…During the last few years, there has been an increase in interest concerning the immunomodulating role of vitamin D [25,222]. Firstly, several observational and cross-sectional studies included in three meta-analyses showed that IBD patients presented low serum vitamin D levels compared to healthy people [183,223,224].…”
Section: Vitamin Dmentioning
confidence: 99%